Temperature response type bionic anti-scaling coating and preparation method thereof

By dynamically deforming and stripping mineral deposits through the temperature-responsive bionic anti-scaling coating, the problems of poor stability and environmental pollution risks in existing technologies are solved, and efficient and safe dynamic anti-scaling and anti-fouling effects are achieved.

CN120718540AActive Publication Date: 2025-09-30TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511211814.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-09-30
Estimated Expiration
2045-08-28

AI Technical Summary

Technical Problem

Existing surface engineering technologies have problems with poor stability, easy loss and potential environmental pollution risks in preventing mineral deposition, especially in water systems, especially in industrial and medical fields.

Method used

A temperature-responsive bionic anti-fouling coating is used, and the coating surface dynamically deforms under temperature changes. The difference in Young's modulus between the deformation-inducing layer and the anti-fouling layer is used to achieve dynamic stripping of mineral deposition. The coating is flat above 35°C and becomes wrinkled below 35°C. The deformation is used to provide mechanical stress to remove deposited minerals.

Benefits of technology

It achieves efficient, stable and safe dynamic anti-scaling and anti-fouling. The coating can be recycled repeatedly under temperature changes. The descaling efficiency is as high as 98%, and no external energy input is required, avoiding the defects of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120718540A_ABST
    Figure CN120718540A_ABST
Patent Text Reader

Abstract

The invention discloses a temperature response type bionic anti-scaling coating and a preparation method thereof. The bionic anti-scale coating comprises a deformation induction layer used for responding to temperature changes and an anti-scale and anti-fouling layer located on the deformation induction layer. The Young modulus of the anti-scale and anti-fouling layer is more than 2000 times that of the deformation induction layer; the thermal expansion coefficient of the deformation induction layer is gt; 100 ppm / DEG C; the bionic anti-scaling coating has the following dynamic morphology changes after the environment temperature changes: 1) when the environment temperature is reduced from T1 to T2, the bionic anti-scaling coating is changed from a flat state to a wrinkled state; (2) the environment temperature is increased to T1 from T2, the bionic anti-scaling coating is changed into a flat state from a wrinkled state, the temperature T1 is 35 DEG C or above, the temperature T2 is smaller than 35 DEG C, and the difference between T1 and T2 is 5 DEG C or above. Under the influence of temperature change, the bionic anti-scaling coating achieves descaling and antifouling by means of dynamic deformation of wrinkles on the surface of the coating and interfacial stress stripping of deposited minerals with high Young modulus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and more specifically to a temperature-responsive bionic anti-scaling coating and a preparation method thereof. Background Art

[0002] Water systems typically contain a large number of mineral ions. These ions form through surface-induced nucleation or environmental changes leading to supersaturated precipitation, resulting in deposition on surfaces such as equipment. Mineral deposition impacts numerous areas of society, including industrial production, healthcare, and energy utilization. In industrial production, mineral deposition often leads to pipe blockages, equipment failures, energy loss, and even safety concerns. In healthcare, when medical catheters are exposed to bodily fluids such as urine, mineral ions (calcium and magnesium ions) in the water can bind to biofilms and deposit within the lumen, significantly increasing the risk of blockage and subsequent infection.

[0003] Surface engineering technology has become an advanced antifouling and anti-scaling method due to its ease of preparation, high efficiency, and durability. However, existing surface engineering technologies, such as those using superhydrophobic materials, superhydrophilic materials, materials that superwet oil layers, and materials that release inhibitors, generally suffer from the problem that the surface air and oil layers are easily lost in the water due to dissolution or scouring, resulting in reduced antifouling effectiveness. Furthermore, the oil layer and released inhibitors pose potential risks to the environment and human health. Zhang et al. (Prog. Org. Coat. 2025, 200, 108992) utilized a microcapsule oil storage / release strategy to replenish the oil layer on the surface for long-term antifouling. However, the oil storage capacity within the microcapsules limits their useful life, and lost oil also poses a burden and risk to the environment. Wang et al. (Adv. Mater. 2023, 35, 2209796) employed an external air replenishment strategy to replenish the surface air layer. However, the high buoyancy of air and the difficulty of replenishing the surface air layer after it is replaced by water limit the coating's usefulness. Therefore, it is of great significance to develop a long-term stable, safe and reliable anti-adhesion coating. Summary of the Invention

[0004] To address the problems existing in the prior art, the first objective of the present invention is to provide a temperature-responsive biomimetic anti-fouling coating. This biomimetic anti-fouling coating utilizes dynamic surface wrinkle deformation (from flat to wrinkled) under the influence of temperature changes, creating interfacial stress to strip high-Young's modulus sedimentary minerals, achieving scale and anti-fouling properties. This coating exhibits efficient, stable, refill-free, safe, and environmentally friendly dynamic anti-fouling capabilities.

[0005] The second object of the present invention is to provide a method for preparing the temperature-responsive bionic anti-fouling coating as described above.

[0006] In order to achieve the above first object, the present invention adopts the following technical solutions: The present invention discloses a temperature-responsive bionic anti-scaling coating, which comprises a deformation-inducing layer for responding to temperature changes and an anti-scaling and anti-fouling layer located above the deformation-inducing layer; The Young's modulus of the anti-fouling layer is more than 2000 times that of the deformation inducing layer; The thermal expansion coefficient of the deformation inducing layer is greater than 100 ppm / °C; The bionic anti-fouling coating exhibits the following dynamic morphological changes after the ambient temperature changes: 1) When the ambient temperature drops from T1 to T2, the bionic anti-fouling coating changes from a flat state to a wrinkled state; 2) When the ambient temperature rises from T2 to T1, the bionic anti-fouling coating changes from a wrinkled state to a flat state; The temperature T1 is above 35°C, the temperature T2 is below 35°C, and the difference between T1 and T2 is above 5°C.

[0007] Furthermore, the bionic anti-scaling coating is flat when the ambient temperature is above 35°C. Below 35°C (excluding 35°C), the coating wrinkles. The lower the temperature, the more wrinkled the coating becomes. Further cooling below room temperature does not significantly change the wrinkles. This design takes into account that in daily life, scale accumulation begins to accelerate at around 40°C, and long-term temperature cycles can produce stubborn scale. Existing surface super-wetting materials have gas and oil layers, and the release of substances is easily lost in dynamic environments. This causes most surfaces to lose their anti-scaling and anti-fouling capabilities after long-term use, posing environmental and biosafety risks. Therefore, the bionic anti-scaling coating of the present invention can be dynamically deformed within the temperature range of room temperature to 40°C to achieve scale removal and anti-fouling. Specifically, when the coating surface is above 35°C for a long time, the coating is in a flat state and scale is continuously deposited. After the temperature drops (the drop is more than 5°C), it becomes a wrinkled state. The surface deformation provides mechanical stress to cause the shedding of high Young's modulus deposited minerals to achieve scale removal. When the ambient temperature rises to above 35°C again, the coating will return to a flat state. Compared with traditional static surfaces that rely on chemical substances and gas / oil layers, it is more stable and efficient, and can be safe and environmentally friendly dynamic anti-scaling and anti-fouling.

[0008] The large difference in Young's modulus formed between the anti-fouling and anti-scaling layer and the deformation inducing layer can ensure the formation of the wrinkled structure. In a specific embodiment, the Young's modulus of the anti-fouling and anti-scaling layer is more than 3,000 times, more than 5,000 times, more than 10,000 times, more than 15,000 times, more than 20,000 times or more than 30,000 times the Young's modulus of the deformation inducing layer.

[0009] Controlling the thermal expansion coefficient of the deformation-inducing layer allows it to exhibit minimal thermal expansion and contraction properties, enabling it to reversibly transform from flat to wrinkled after changes in ambient temperature. It's important to note that if the ambient temperature change is too small, it may cause minor deformation, affecting the descaling effect. A temperature difference of 5°C or more (preferably 10°C or more) is recommended. For example, in a household electric water heater, the surface of the bionic anti-scaling coating is flat at 37°C and wrinkled at room temperature. As the ambient temperature rises from room temperature to 37°C, the wrinkles gradually transform into flat surfaces, and as the temperature drops from 37°C to room temperature, the flat surfaces gradually transform into wrinkles. This dynamic wrinkle deformation provides stress and achieves descaling. In one embodiment, the thermal expansion coefficient of the deformation-inducing layer is 250-400 ppm / °C.

[0010] Furthermore, the thickness of the deformation inducing layer is not less than 100 μm, preferably 100-300 μm; The thickness of the anti-fouling and anti-scaling layer is 20-100 nm.

[0011] Furthermore, the wavelength of the wrinkle structure in the wrinkled state is 1-300 µm, and the amplitude is 0.1-20 µm. The wavelength and amplitude of the wrinkle structure are mainly related to the thickness of the anti-fouling and anti-scaling layer, the Young's modulus of the deformation-inducing layer, and temperature changes. When the thickness of the anti-fouling and anti-scaling layer increases, the amplitude and wavelength of the wrinkle structure increase. As the thickness increases from 20 nm to 100 nm, the amplitude of the wrinkle structure increases from 0.1 µm to 1.1 µm, and the wavelength increases from 1 µm to 10 µm. When the modulus of the deformation-inducing layer changes from 42 kPa to 2.1 MPa, the amplitude and wavelength of the wrinkles increase as the modulus decreases. As the modulus decreases from 2.1 MPa to 42 kPa, the amplitude increases from 1.1 µm to 20 µm, and the wavelength increases from 10 µm to 300 µm. As the temperature drops, the amplitude of the wrinkles increases, while the wavelength barely changes. From 37°C to room temperature (24°C), wrinkles gradually appear and their amplitude increases. This combined effect ultimately allows for precise control of wrinkle structure from nanometers to micrometers.

[0012] Furthermore, the Young's modulus of the anti-fouling and anti-scaling layer is 520 MPa-168 GPa; The Young's modulus of the deformation inducing layer is 42 kPa-2.1 MPa.

[0013] Furthermore, the deformation inducing layer is obtained by curing a monomer and a cross-linking agent; The monomers are selected from polydimethylsiloxane 184 and / or silicone rubber ecoflex 00-30. Since the above monomers are commercially available products, the crosslinking agents selected can be products that are compatible with the monomers.

[0014] Furthermore, the anti-fouling and anti-scaling layer contains functional thin film materials, which can be divided into two categories, including inorganic metal materials such as platinum nanoparticles and silver nanoparticles, and one or more organic rigid polymers such as polyethylene glycol dimethacrylate, polyhydroxyethyl methacrylate, polyvinyl alcohol, 4-vinylbenzyl anthracene methyl ether-n-butyl acrylate copolymer.

[0015] In order to achieve the above second purpose, the present invention adopts the following technical solutions: The present invention discloses a method for preparing the bionic anti-fouling coating as described above, comprising the following steps: Mix the monomer and the matching cross-linking agent in proportion to obtain a coating solution; The coating liquid is spin-coated on the substrate, and a semi-cured deformation-inducing layer is obtained after pre-curing; The supporting material is infiltrated into the semi-cured deformation inducing layer, and after it is completely cured, the bionic anti-fouling coating is obtained.

[0016] Furthermore, the mass ratio of the monomer to the matching cross-linking agent is 1:1-1:10, and the Young's modulus of the coating obtained with different mass ratios is different. The wavelength and amplitude of the wrinkle structure can be controlled by controlling the mass ratio of the monomer to the matching cross-linking agent.

[0017] Furthermore, depending on the different functional film materials, the support material is infiltrated into the semi-solidified deformation inducing layer by vapor deposition or coating.

[0018] Furthermore, the parameters of vapor deposition were 20 mA and the vacuum degree was less than 4.0 Pa; The mass fraction of the solution containing the functional film material prepared during coating is 1-5%.

[0019] The beneficial effects of the present invention are as follows: The temperature-responsive bionic anti-scaling coating prepared by the present invention includes a deformation-inducing layer for responding to temperature changes and an anti-scaling and anti-fouling layer located above the deformation-inducing layer. In response to changes in ambient temperature, the bionic anti-scaling coating dynamically switches between a wrinkled state and a flat state, providing interfacial stress to actively peel off mineral dirt. The triggering of dynamic wrinkle interface deformation is environmentally adaptable (e.g., ambient temperature changes, with a temperature variation range of 5°C or more) to achieve dynamic wrinkle changes, without the need for additional external energy (such as electric or magnetic fields) to avoid potential risks. This environmentally adaptable interface deformation introduces interfacial stress, causing the shedding of deposited high-Young's modulus minerals, overcoming the shortcomings of traditional static surface protection, which relies on chemical release and unstable gas / oil layers.

[0020] The bionic anti-scaling coating of the present invention can achieve precise regulation of the wrinkle structure from nanometers to micrometers through precise regulation. In the wrinkled state, the wavelength of the wrinkle structure is 1-300 μm and the amplitude is 0.1-20 μm.

[0021] In a 120-hour mineral experiment in a supersaturated mineral salt solution, the bionic anti-scaling coating surface of the present invention has a scale removal efficiency of 98% compared to a static plane, and the scale deposition amount is controlled at 0.05 mg / cm 2 The mineral deposition on the static surface reached 2.5 mg / cm 2 .

[0022] The preparation method of this bionic anti-fouling coating is simple and convenient. The strong interaction between the deformation-inducing layer and the anti-fouling layer ensures the high stability of the material, and can achieve repeated environmentally adaptive dynamic deformation.

[0023] The present invention overcomes the problems of easy failure and secondary contamination of existing surface protective layers by introducing stress into the interface anti-scaling design through surface dynamic deformation, and provides a new type of efficient, long-lasting, safe and reliable anti-scaling solution. It is expected to be applied in scenarios with fluctuating ambient temperatures, such as industrial water systems, water heater systems (including pipes and shower heads) and medical catheters. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0025] Figure 1 A confocal image of three-dimensional wrinkles of the biomimetic antifouling coating of Example 1 is shown.

[0026] Figure 2 The image shows the interface deformation of the environmentally adaptable bionic anti-fouling coating prepared in Example 1 as the ambient temperature changes.

[0027] Figure 3 An image showing that the environmentally adaptable bionic anti-fouling coating prepared in Example 5 undergoes interfacial deformation to provide stress and achieve mineral stripping. DETAILED DESCRIPTION

[0028] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the following detailed description is illustrative rather than restrictive and should not be used to limit the scope of protection of the present invention.

[0029] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0030] Example 1 A double-layer biomimetic antifouling coating was prepared by selecting an anti-fouling layer (an inorganic nano-platinum layer with a Young's modulus of 168 GPa) and a deformation-inducing layer (prepared by polydimethylsiloxane 184 and a cross-linking agent at a mass ratio of 10:1, with a Young's modulus of 2.1 MPa after cross-linking) with a Young's modulus difference of more than 3000 times. The steps are as follows: 1) Mix polydimethylsiloxane 184 and crosslinker at a mass ratio of 10:1 and remove bubbles; 2) Spin coating the material from step 1) on the substrate at room temperature at a spin coating speed of 1000 rpm / min for 30 seconds, and pre-curing the material at 60°C for 15-30 minutes to obtain a semi-cured deformation inducing layer; 3) On the basis of the semi-solid deformation inducing layer of step 2), inorganic platinum nanoparticles are vapor-deposited by ion sputtering (current of 20 mA, vapor deposition time of 540 s) to form an inorganic nano-platinum layer. The inorganic nano-platinum layer can penetrate into the semi-solid deformation inducing layer to form a mechanical interlocking structure; 4) The semi-cured composite coating in step 3) is treated at a temperature of 37-60°C for 12 hours to fully cure, thereby obtaining an environmentally adaptable bionic anti-fouling coating, wherein the thickness of the deformation-inducing layer is 100 µm, and the thickness of the inorganic nano-platinum layer is 100 nm. The surface changes of the bionic anti-fouling coating are captured by changing the temperature range, such as Figure 1 and Figure 2 As shown, when the temperature is 37°C, the coating is in a flat state. When the temperature drops to 24°C, the coating is in a wrinkled state. The cyclicity of dynamic wrinkles (flat-wrinkled-flat-wrinkled) can also be observed, which can be repeated many times. The amplitude is 1.10 µm and the wavelength is 10.33 µm.

[0031] Example 2 The preparation process is the same as that in Example 1, except that the vapor deposition time is extended to 120 s and the thickness of the inorganic nano-platinum layer is adjusted to 22 nm. The prepared bionic anti-scaling coating can also achieve the same dynamic deformation of wrinkles as in Example 1, with an amplitude of 0.14 μm and a wavelength of 2.47 μm.

[0032] Example 3 The preparation process was the same as that in Example 1, except that the mass ratio of polydimethylsiloxane 184 to the cross-linking agent was adjusted to 20:1, so that the Young's modulus of the deformation-inducing layer was changed to 680 kPa. The prepared bionic anti-fouling coating could also achieve the same dynamic wrinkle deformation as in Example 1, with an amplitude of 1.85 μm and a wavelength of 35.57 μm.

[0033] Test Example 1 The anti-scaling performance of the biomimetic anti-scaling coatings prepared in Examples 1-3 was tested by placing the substrate coated with the coating to be tested in a supersaturated calcium sulfate mineral solution at a temperature that simulates the temperature range of industrial cooling water or water heaters (24-37°C). The mineral deposition was observed after 120 hours. The results showed that the mineral deposition amounts on Examples 1, 2, and 3 were 0.026 mg / cm 2 , 0.045 mg / cm 2 and 0.039 mg / cm 2 It was found that there was almost no mineral deposition on the coating surface of each embodiment, and the mineral content on the coating surface was less than 0.05 mg / cm 2 The bionic anti-scaling coating shows a good anti-scaling effect. This effect comes from the dynamic surface temperature dropping from 37°C to 24°C. The stress provided in the process of the plane becoming a wrinkle realizes the self-peeling of minerals and the surface, thereby resisting mineral deposition.

[0034] The coatings in Examples 1-3 were placed in a supersaturated mineral solution at a temperature that simulates the temperature changes of a water heater (24-37°C, with a temperature change rate of approximately 1°C / 3min) for up to one month to observe the stability of the underwater dynamic wrinkling coating against mineral adhesion. It was found that the coatings still maintained good anti-scaling performance after 30 days, and the cyclic performance of the dynamic wrinkling was stable.

[0035] Comparative Example 1 The preparation process was the same as that in Example 1, except that the mass ratio of polydimethylsiloxane 184 to the cross-linking agent was adjusted to 50:1, so that the Young's modulus of the deformation-inducing layer was changed to 42 kPa. The prepared bionic anti-fouling coating could also achieve the same dynamic wrinkle deformation as in Example 1, with an amplitude of 27.41 μm and a wavelength of 265.41 μm.

[0036] The anti-fouling performance of the coating prepared in Comparative Example 1 was tested by placing the substrate coated with the coating in a supersaturated calcium sulfate mineral solution at a temperature that simulated the temperature range of industrial cooling water or water heaters (24-37°C). The mineral deposition was observed after 120 hours. The results showed that the mineral deposition on Comparative Example 1 reached 4.57 mg / cm 2 , far exceeding 0.05 mg / cm 2 , it is difficult to achieve good anti-fouling effect.

[0037] Example 4 A double-layer biomimetic antifouling coating was prepared by selecting an antifouling layer (composed of polyethylene glycol dimethacrylate, with a Young's modulus of 520 MPa) and a deformation-inducing layer (prepared from silicone rubber ecoflex00-30 and a cross-linking agent in a mass ratio of 1:1, with a Young's modulus of 0.17 MPa) with a Young's modulus difference of much greater than 3000 times. The steps are as follows: 1) Mix silicone rubber ecoflex00-30 monomer and crosslinker in a mass ratio of 1:1 and remove bubbles; 2) Spin coating the material from step 1) on the substrate at room temperature at a spin coating speed of 1000 rpm / min for 30 seconds, and pre-curing the material at 60°C for 15-30 minutes to obtain a semi-cured deformation inducing layer; 3) dissolving polyethylene glycol dimethacrylate in toluene solvent to form an organic solution with a mass fraction of 1%, and spin-coating the organic solution on the semi-cured deformation-inducing layer in step 2) to form an organic layer. The spin coating rate is 1000 rpm / min for 60 seconds. The organic layer can penetrate into the semi-cured deformation-inducing layer to form a mechanical interlocking structure. 4) The semi-cured composite coating obtained in step 3) was left at room temperature for 6 h to fully cure, resulting in an environmentally adaptable bionic anti-fouling coating. The thickness of the deformation-inducing layer was 100 µm, and the thickness of the organic layer was 26 nm. The surface changes of the bionic anti-fouling coating were captured by varying the temperature range. When the temperature was above 37°C, the coating was flat. When the temperature was lowered to room temperature, the coating was wrinkled. The cyclicity of dynamic wrinkles (flat-wrinkled-flat-wrinkled) was also observed, and the cycle could be repeated multiple times. The amplitude was 0.15 µm and the wavelength was 1.86 µm.

[0038] Example 5 The preparation process was the same as that in Example 4, except that the mass fraction of the organic solution was increased to 5%, so that the thickness of the obtained organic layer became 78 nm. The prepared bionic anti-fouling coating could also achieve the same dynamic wrinkle deformation as in Example 4, with an amplitude of 0.99 µm and a wavelength of 10.11 µm.

[0039] Test Example 2 The descaling performance of the biomimetic anti-scaling coating prepared in Example 4-5 was tested, specifically by placing the substrate coated with the coating to be tested in a supersaturated calcium sulfate mineral solution at a temperature of 37° C. for 24 h. Figure 3 In the biomimetic anti-scaling coating of Example 5, minerals are deposited on the flat biomimetic anti-scaling coating. When the temperature drops to room temperature, the biomimetic anti-scaling coating actively peels off the surface minerals through the stress generated by dynamic deformation. The amount of mineral deposited on the sample of Example 4 increases from 3.74 mg / cm 2 Reduced to 0.07 mg / cm2 The mineral removal rate reached 98%, and the mineral deposition on the sample of Example 5 was reduced from 4.09 mg / cm 2 Reduced to 0.04 mg / cm 2 The mineral removal rate reached 99%, and the minerals deposited after changes in the external environment were removed.

[0040] The cyclic descaling performance of the bionic anti-scaling coating prepared in Examples 4-5 was tested. The specific steps were as follows: the substrate coated with the coating to be tested was placed in a supersaturated calcium sulfate mineral solution at a temperature of 37°C for 24 hours. The minerals were deposited on the flat bionic anti-scaling coating. When the temperature dropped to room temperature, the bionic anti-scaling coating actively peeled off the minerals on the surface through the stress generated by dynamic deformation. The above steps were repeated for 6 cycles of scaling at 37°C and descaling at room temperature. It was found that Examples 4 and 5 both maintained a mineral removal rate of more than 98%.

[0041] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A temperature-responsive bionic anti-scaling coating, characterized in that: The bionic anti-fouling coating comprises a deformation-inducing layer for responding to temperature changes and an anti-fouling and anti-scaling layer located on the deformation-inducing layer; The Young's modulus of the anti-fouling layer is more than 2000 times that of the deformation inducing layer; The thermal expansion coefficient of the deformation inducing layer is greater than 100 ppm / °C; The bionic anti-fouling coating exhibits the following dynamic morphological changes after the ambient temperature changes: 1) When the ambient temperature drops from T1 to T2, the bionic anti-fouling coating changes from a flat state to a wrinkled state; 2) When the ambient temperature rises from T2 to T1, the bionic anti-fouling coating changes from a wrinkled state to a flat state; The temperature T1 is above 35°C, the temperature T2 is below 35°C, and the difference between T1 and T2 is above 5°C.

2. The bionic anti-fouling coating according to claim 1, characterized in that The Young's modulus of the anti-fouling and anti-scaling layer is more than 3000 times that of the deformation inducing layer.

3. The bionic anti-fouling coating according to claim 1, characterized in that The thickness of the deformation inducing layer is not less than 100 μm; The thickness of the anti-fouling and anti-scaling layer is 20-100 nm.

4. The bionic anti-fouling coating according to claim 1, characterized in that The wavelength of the wrinkle structure in the wrinkle state is 1-300 µm, and the amplitude is 0.1-20 µm.

5. The bionic anti-fouling coating according to claim 1, characterized in that The Young's modulus of the anti-fouling and anti-scaling layer is 520 MPa-168 GPa; The Young's modulus of the deformation inducing layer is 42 kPa-2.1 MPa.

6. The bionic anti-fouling coating according to claim 1, characterized in that The deformation inducing layer is obtained by curing a monomer and a cross-linking agent; The monomer is selected from polydimethylsiloxane 184 and / or silicone rubber ecoflex00-30.

7. The bionic anti-fouling coating according to claim 1, characterized in that The anti-fouling and anti-scaling layer contains functional film materials, which include one or more of platinum nanoparticles, silver nanoparticles, polyethylene glycol dimethacrylate, polyhydroxyethyl methacrylate, polyvinyl alcohol, and 4-vinylbenzyl anthracene methyl ether-n-butyl acrylate copolymer.

8. A method for preparing a bionic anti-fouling coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mix the monomer and the matching cross-linking agent in proportion to obtain a coating solution; The coating liquid is spin-coated on the substrate, and a semi-cured deformation-inducing layer is obtained after pre-curing; The functional film material is infiltrated into the semi-cured deformation inducing layer, and after it is completely cured, the bionic anti-fouling coating is obtained.

9. The preparation method according to claim 8, characterized in that Depending on the functional film material, the functional film material is infiltrated into the semi-solidified deformation inducing layer by vapor deposition or coating.

10. The preparation method according to claim 9, characterized in that The parameters of vapor deposition were 20 mA and the vacuum degree was less than 4.0 Pa; The mass fraction of the solution containing the functional film material prepared during coating is 1-5%.

Citation Information

Patent Citations

  • Devices and methods for active biofouling control

    CN104144709A

  • Anti-icing material with low ice adhesion strength and high desorption speed as well as preparation method and application of anti-icing material

    CN116925642A

  • Rapid self-driven anti-icing material and preparation method thereof

    CN119242266A

  • Composite material as well as preparation method and application thereof

    CN119286036A

  • Shape adaptive wrinkle-driven 3D tubular structure for stretchable interactive electronics

    US20210053329A1